1958
DOI: 10.1515/znb-1958-0607
|View full text |Cite
|
Sign up to set email alerts
|

Instabile CO2-Fixierung und Photosynthese

Abstract: Das Ergebnis war in allen Versuchen identisch: i2P aus biologisch markiertem, isoliertem /?-32P-Lipoproteid war auch im vorher unmarkierten ax-Instabile CCVFixierung und Photosynthese V on H e l m u t M e t z n e r * , H e l m u t S im

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1959
1959
1965
1965

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Metzner et al (356,357) have reported that new labile fixation products are obtained when illuminated algae suspensions are fixed with cold acetone. Kandler (358) has communicated experiments according to which the kill ing of algae, usually performed with hot alcohol, probably simulates a too high fixation of 14C02 in phosphoglyceric acid.…”
Section: Photosynthesismentioning
confidence: 99%
“…Metzner et al (356,357) have reported that new labile fixation products are obtained when illuminated algae suspensions are fixed with cold acetone. Kandler (358) has communicated experiments according to which the kill ing of algae, usually performed with hot alcohol, probably simulates a too high fixation of 14C02 in phosphoglyceric acid.…”
Section: Photosynthesismentioning
confidence: 99%
“…25 There have since been many attempts to extend the relation to more concentrated suspensions, generally by adding terms of higher powers of +. 26 It is significant that these relations all show the relative viscosity to depend only on 4 and not in any way on the particle size.…”
Section: Relation Of Gel-containing Materials To Master Batchmentioning
confidence: 95%
“…However, the latter difference should not void qualitative conclusions, and sufficient normal stress measurements are available to assess the general magnitude of the Weissenberg number; for highly viscoelastic polymer solutions possessing low values of the parameters n and s it is likely to be in the range of 10 to 100 under conditions of interest (7,17,18,23,28,52, 5 4 ) . For such fluids, reference to Table 1 shows that appreciable increases in length of the entry region are predicted.…”
Section: +Sbs" ( 2 + N -S S N -S ) ] ( 3 0 )mentioning
confidence: 99%
“…From the kinematic analysis of White and Metzner (59) and Equation (18), one may, however, show that…”
Section: Constitutive Relationships For Evaluation Of Stressesmentioning
confidence: 99%